2019
DOI: 10.1038/s41575-019-0210-2
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive immunity: an emerging player in the progression of NAFLD

Abstract: In the past decade, nonalcoholic fatty liver disease (NAFLD) has become a leading cause of chronic liver disease and cirrhosis, as well as an important risk factor for hepatocellular carcinoma (HCC). NAFLD encompasses a spectrum of liver lesions, including simple steatosis, steatohepatitis and fibrosis. Although steatosis is often harmless, the lobular inflammation that characterizes nonalcoholic steatohepatitis (NASH) is considered a driving force in the progression of NAFLD. The current view is that innate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
245
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(281 citation statements)
references
References 133 publications
(263 reference statements)
9
245
0
5
Order By: Relevance
“…(70) Although innate immune mechanisms are considered a major contributing factor to the inflammatory process in NASH, recent evidence indicates that adaptive immunity has an important role in the progression of this disease. (71) Here, we highlight the major immune cell types involved in the progression of NASH.…”
Section: Mechanisms Of Inflammation Inflammation and Immune Dysregulamentioning
confidence: 99%
“…(70) Although innate immune mechanisms are considered a major contributing factor to the inflammatory process in NASH, recent evidence indicates that adaptive immunity has an important role in the progression of this disease. (71) Here, we highlight the major immune cell types involved in the progression of NASH.…”
Section: Mechanisms Of Inflammation Inflammation and Immune Dysregulamentioning
confidence: 99%
“…NAFLD is emerging as a worldwide public health threat (31). A number of patients with NAFLD develop a more inflammatory and progressive subtype-NASH, which can lead to cirrhosis and end-edge liver disease (32,33). The cornerstones of NAFLD treatment are weight loss and increased amounts of exercise, but maintaining these lifestyle changes can be hard.…”
Section: Discussionmentioning
confidence: 99%
“…65,66 The lack of adaptive immunity in HLCM may also pose questions about its reliability for the study of metabolic liver disease and drug-induced liver injury (DILI) in certain aspects. [67][68][69][70] Fortunately, recent seminal studies have shown a framework that would alleviate this fundamental constraint by reconstituting the hu-manized adaptive immune system. 12,[71][72][73][74][75][76] This approach requires the transplantation of hematopoietic stem cells, preferably with the concurrent transplantation of bone marrow, spleen, and thymus from the same donor to reestablish the human adaptive immune system in HLCM.…”
Section: Current Limitations and Progress In Overcoming Themmentioning
confidence: 99%